2002
DOI: 10.1063/1.1456544
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of the deep Mn acceptor in GaN:Mn

Abstract: Articles you may be interested inDeep level transient spectroscopy in plasma-assisted molecular beam epitaxy grown Al 0.2 Ga 0.8 N / GaN interface and the rapid thermal annealing effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
103
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 17 publications
14
103
0
2
Order By: Relevance
“…However, an essential ingredient of this model is a p-type carrier concentration of around 10 20 cm -3 , a value significantly higher than the highest hole concentrations so far obtained in GaN. Furthermore, optical measurements have indicated that the Mn acceptor level lies over 1eV above the valence band maximum in Wurtzite (Ga,Mn)N [9,10], which is in agreement with density-of-states calculations [11]. Therefore, in contrast to the case for (Ga,Mn)As, Mn does not appear to be an efficient acceptor in Wurtzite GaN, and may not be expected to interact strongly with delocalised charge carriers in the conduction or valence bands.…”
Section: Introductionmentioning
confidence: 99%
“…However, an essential ingredient of this model is a p-type carrier concentration of around 10 20 cm -3 , a value significantly higher than the highest hole concentrations so far obtained in GaN. Furthermore, optical measurements have indicated that the Mn acceptor level lies over 1eV above the valence band maximum in Wurtzite (Ga,Mn)N [9,10], which is in agreement with density-of-states calculations [11]. Therefore, in contrast to the case for (Ga,Mn)As, Mn does not appear to be an efficient acceptor in Wurtzite GaN, and may not be expected to interact strongly with delocalised charge carriers in the conduction or valence bands.…”
Section: Introductionmentioning
confidence: 99%
“…In the optical characterization of ͑Ga,Mn͒N, photoluminescence ͑PL͒ peaks were observed at 2.5 and 3.0 eV in Mn-implanted and annealed GaN. 11 The Mn impurities in GaN, acting as a deep acceptor for electrons at an energy level of E v ϩ1.4 eV, played a role in strongly disordering the lattice structure. 12 Despite a number of works mentioned above, no experimental evidence on the effects of such secondary phases and lattice imperfections on both the ferromagnetic and optical properties in GaN-based DMS was provided because of lack of experimental resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental [34][35][36] and density functional theory (DFT) studies [37][38][39][40][41][42] demonstrated a partially filled impurity band formed deeply in the band gap with a significant Mn d character, suggesting a Mn 3+ (d 4 ) configuration different from the Mn 2+ (d 5 ) one in Ga 1−x Mn x As [43]. Later, both x-ray absorption spectroscopy (XAS) studies [44][45][46] and optical absorption analysis [47,48] also concluded a Mn valence state of 3+ (d 4 ).…”
mentioning
confidence: 99%